High-strength wear-resistant composite plastic with high auxiliary material content and preparation method of high-strength wear-resistant composite plastic
Through the esterification reaction of modified plasticizers and fillers, the cross-linking ability and compatibility of composite plastics are improved, and the problem of insufficient wear resistance and strength of existing high-strength plastics is solved, achieving high strength, wear resistance and resistance Stretch and flame retardant composite plastic.
Patent Information
- Application Number
- CN202411421042.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The wear resistance and strength of existing high-strength plastics need to be further improved, and the toughening agent content is too low during processing and low material compatibility, resulting in limited room for performance improvement.
Using modified plasticizers and modified fillers, the cross-linking capacity and compatibility of composite plastics are improved through esterification reaction, chain extension, end capping and cross-linking steps, and epoxy groups are added to form a flame retardant layer. Improve the wear resistance, tensile resistance and flame retardant properties of plastics.
It significantly improves the wear resistance, tensile resistance and flame retardant properties of composite plastics, forming high-strength, wear resistance, tensile resistance and flame retardant composite plastics.
Smart Images

Figure BDA0005080786650000021 
Figure BDA0005080786650000031 
Figure BDA0005080786650000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic processing, and in particular to a high-strength wear-resistant composite plastic with high auxiliary material content and a preparation method thereof. Background Art
[0002] The development history of high-strength wear-resistant plastics with high auxiliary material content began with basic research and early reinforcement material applications in the mid-20th century. In the 1970s and 1980s, formulation optimization became the key, and high-filler plastics were developed. The mechanical properties of plastics were significantly improved by adding a large amount of fillers such as mineral powders and glass fibers. From the 1990s to the early 21st century, the research focus shifted to the application of high-performance fillers. For example, the introduction of nanomaterials significantly improved the strength, wear resistance and thermal stability of plastics. At the same time, advanced processing technologies, such as high-precision injection molding and extrusion molding, further improved product quality. Entering the 21st century, the focus of the modern stage is on the development of functional and intelligent materials, including self-healing materials and high-strength wear-resistant plastics with antibacterial functions. These innovations meet more demanding application requirements. In addition, environmental protection and sustainability have become important trends, promoting the research of recyclable materials and bio-based plastics, which are not inferior to traditional materials in performance while reducing environmental impact.
[0003] Prior art CN108795082A discloses a high-strength plastic, comprising the following raw materials in parts by weight: 66-88 parts of monomer resin, 5-6 parts of plasticizer, 0.8-1.6 parts of heat stabilizer, 3.5-5.5 parts of toughening agent, 6-18 parts of calcium carbonate and 12-26 parts of carbon black, so that the plastic has a higher strength, increases the application occasions of the plastic, has high strength and high toughness, and extends the service life of the plastic.
[0004] Although the above-mentioned disclosure achieves the purpose of enhancing the performance of plastics by improving the plastic formula ratio, the content of toughening agent is too low during the processing, and the room for improving the strength and toughness of the plastics is limited. Secondly, the monomer resin or inorganic materials calcium carbonate and carbon black are not modified during the processing. Due to the large polarity between the two, the compatibility between the materials is low, thereby reducing the strength of the plastic. That is, the strength of the plastic products obtained by optimizing the formula ratio needs to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a high-strength wear-resistant composite plastic with a high auxiliary material content and a preparation method thereof, so as to solve the technical problem that the wear resistance and strength of the composite plastic in the prior art need to be further improved.
[0007] The object of the present invention can be achieved by the following technical scheme: a high-strength wear-resistant composite plastic with a high auxiliary material content, comprising the following components in parts by weight: 40-50 parts of a plastic matrix, 30-40 parts of a modified plasticizer, 20-30 parts of a modified filler, 5-8 parts of a stabilizer, 5-8 parts of an antioxidant, 5-8 parts of an ultraviolet absorber and 5-8 parts of a lubricant;
[0008] The preparation method of the modified plasticizer comprises the following steps:
[0009] A1, adding modified polyester, cyanuric acid, 0.5-2.0wt% sodium hydroxide solution and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 60-80°C, keeping the temperature for 4-6h, and post-treating to obtain chain-extended polyester;
[0010] The reaction equation for preparing chain-extended polyester is:
[0011]
[0012] Where:
[0013] The reaction principle for preparing chain-extended polyester is as follows: under alkaline conditions, the carboxyl group of the modified polyester and the hydroxyl group of cyanuric acid undergo esterification reaction to form polyester-embedded organic chain segments. After the reaction, the molecular structure of the modified polyester is effectively chain-extended, and finally a chain-extended polyester with enhanced performance is generated.
[0014] A2, adding chain-extended polyester, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 50-60° C., keeping the temperature for reaction for 1-2 hours, and post-treating to obtain a capped polyester;
[0015] The reaction equation for preparing end-capped polyester is:
[0016]
[0017] Where:
[0018] The reaction principle for preparing the end-capped polyester is as follows: under the catalysis of triethylamine, the epoxy group on 3-(2,3-epoxypropoxy)propyltrimethoxysilane and the carboxyl group on the chain-extended polyester undergo a ring-opening reaction, the chain-extended polyester is end-capped, and the end-capped polyester cross-linked with a silane coupling agent is formed.
[0019] A3. Add the end-capped polyester, formic acid, hydrogen peroxide and N,N-dimethylformamide into a reaction kettle and stir. The temperature of the reaction kettle is raised to 50-60°C. After stirring for 30-40 minutes, post-treatment is performed to obtain a modified plasticizer.
[0020] The reaction equation for preparing modified plasticizer is:
[0021]
[0022] Where:
[0023] The reaction principle for preparing the modified plasticizer is: formic acid and hydrogen peroxide form peroxy acid in the system, and its excellent oxidation performance cyclizes the carbon-carbon double bond in the blocked polyester to form an epoxy group, thereby obtaining the modified plasticizer.
[0024] Furthermore, in step A1, the amount ratio of the modified polyester, cyanuric acid, 0.5-2.0wt% sodium hydroxide solution and N,N-dimethylformamide is 2-4g:2-4g:15-20mL:15-20mL; in step A2, the amount ratio of the chain extended polyester, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide is 8-10g:2-4g:0.5-0.8g:40-60mL; in step A3, the stirring rate is 80-120rpm, and the amount ratio of the end-capped polyester, formic acid, hydrogen peroxide and N,N-dimethylformamide is 8-10g:1-2g:1-2g:30-40mL.
[0025] Furthermore, in step A1, the post-treatment operation is: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is produced to obtain a chain-extended polyester; in step A2, the post-treatment operation is: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is produced to obtain a capped polyester; in step A3, the post-treatment operation is: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is produced to obtain a modified plasticizer.
[0026] Furthermore, in step A1, the preparation method of the modified polyester is: 4,4'-stilbene dicarboxylic acid, 1,5-hexadiene-3,4-diol, dichlorobenzene and 98.0wt% concentrated sulfuric acid are added to a reactor, the temperature of the reactor is increased to 150-170°C, the reaction is kept warm for 12-16h, and the modified polyester is obtained by post-treatment.
[0027] The reaction equation for synthesizing modified polyester is:
[0028]
[0029] Where:
[0030] The reaction principle of synthesizing modified polyester is as follows: at high temperature, 4,4'-stilbene dicarboxylic acid and 1,5-hexadiene-3,4-diol undergo free radical polymerization reaction under the catalysis of concentrated sulfuric acid. By controlling the amount of the two substances, a modified polyester with carboxyl as the end group is obtained.
[0031] Furthermore, the dosage ratio of the 4,4'-stilbene dicarboxylic acid, 1,5-hexadiene-3,4-diol, dichlorobenzene and 98.0wt% concentrated sulfuric acid is 2-4g:1-2g:20-30mL:0.1-0.2g, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a modified polyester.
[0032] Furthermore, the preparation method of the modified filler comprises the following steps:
[0033] B1. Add graphene oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, triethylamine and ethanol into a reactor and stir. Raise the temperature of the reactor to 50-60° C., keep warm and stir for 1-2 hours, and perform post-treatment to obtain modified graphene.
[0034] Reaction principle: A large number of active functional groups on graphene oxide, such as hydroxyl groups, react with the phosphorus-hydrogen bonds of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, so that 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is cross-linked on the surface and inside of graphene oxide, and finally modified graphene is obtained.
[0035] B2. Add modified graphene, 3-aminopropyltriethoxysilane, zinc chloride and N,N-dimethylformamide into a reactor, increase the temperature of the reactor to 50-60° C., keep the temperature for 30-40 minutes, and perform post-treatment to obtain a modified filler.
[0036] Reaction principle: A large number of active functional groups on the modified graphene, such as carboxyl groups, react with the amino groups of 3-aminopropyltriethoxysilane to form amide bonds. 3-aminopropyltriethoxysilane cross-links with the modified graphene through the amide bonds to finally obtain a modified filler.
[0037] Furthermore, in step B1, the stirring rate is 80-120 rpm, and the amount ratio of the graphene oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, triethylamine and ethanol is 5-8 g:2-3 g:0.5-0.6 g:25-35 mL; in step B2, the amount ratio of the modified graphene, 3-aminopropyltriethoxysilane, zinc chloride and N,N-dimethylformamide is 8-10 g:2-4 g:0.5-0.8 g:40-50 mL.
[0038] Furthermore, in step B1, the post-treatment includes: after the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3-5 times with deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight, thereby obtaining modified graphene; in step B2, the post-treatment includes: after the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3-5 times with deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight, thereby obtaining modified filler.
[0039] Furthermore, the preparation method of graphene oxide is as follows: multilayer graphene and 98.0wt% sulfuric acid are added to a reactor at a temperature of 0-5°C and stirred, and after keeping warm and stirring for 10-15 minutes, sodium chlorate is added to the reactor, and the temperature of the reactor is maintained at 0-5°C for 2-4 hours, and a saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7, and post-treatment is performed to obtain multilayer graphene oxide.
[0040] Reaction principle: Multilayer graphene undergoes partial sulfation reaction, which makes the structure of graphene more active and creates conditions for oxidation reaction. Sodium chlorate will decompose to produce chloric acid and oxygen under acidic conditions. The strong oxidizing effect of chloric acid can oxidize the carbon layer of graphene oxide to produce graphene oxide, which contains various oxygen functional groups, such as epoxy groups, carboxyl groups and hydroxyl groups.
[0041] Furthermore, the amount ratio of the multilayer graphene, 98.0wt% sulfuric acid and sodium chlorate is 5-8g:30-40g:3-5g, the stirring rate is 80-120rpm, and the post-treatment includes: after the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3-5 times with deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain oxidized multilayer graphene.
[0042] The present invention also provides a method for preparing a high-strength wear-resistant composite plastic with a high auxiliary material content, comprising the following steps:
[0043] S1, a plastic matrix, a modified plasticizer, a modified filler, a stabilizer, an antioxidant, an ultraviolet absorber and a lubricant are uniformly mixed to obtain a mixture;
[0044] S2, adding the mixed material to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 180°C, 185, 185°C, 190°C, 190°C, 200°C, 200°C, the main engine speed of the twin-screw extruder is 80-120rpm, the pressure is 100-150bar, and a composite plastic precursor is obtained after melt extrusion;
[0045] S3. Transfer the plastic precursor to a box filled with water vapor, treat it for 6-8 hours, cool it down and discharge it to obtain a composite plastic.
[0046] Furthermore, the plastic matrix is one or more of polytetrafluoroethylene, polyvinyl fluoride and polyvinylidene fluoride, the stabilizer is one or more of diester zinc stabilizer, calcium zinc heat stabilizer HX-10 and lead-free calcium zinc stabilizer LX-800, the antioxidant is one or both of butylated hydroxyanisole and butylated hydroxybenzoic acid, the ultraviolet absorber is UV-531, and the lubricant is one or more of magnesium stearate, calcium stearate, zinc stearate and polyethylene wax.
[0047] The present invention has the following beneficial effects:
[0048] 1. In the process of preparing a high-strength and wear-resistant composite plastic with a high auxiliary material content, the present invention selects to add a large amount of modified plasticizer and modified filler to the resin to improve the strength of the composite plastic, wherein the modified plasticizer and modified filler obtained by modification are modified with a cross-linking agent group, which improves the strength of the composite plastic while improving the cross-linking ability inside the composite plastic, so that the wear resistance of the composite plastic is significantly improved, and the two cooperate with each other during the combustion process, and the flame retardant chain segment modified by the modified auxiliary material at high temperature decomposes and promotes the carbonization of the triazine ring in the modified plasticizer, forming a flame retardant layer and cooperating with the graphene oxide component in the modified filler to improve the flame retardant ability of the composite plastic, and finally a high-strength, wear-resistant, tensile-resistant and flame-retardant composite plastic with a high auxiliary material content is obtained.
[0049] 2. In the process of preparing a high-strength wear-resistant composite plastic with a high auxiliary material content, the present invention first prepares a modified polyester with an olefin double bond and a benzene ring structure, and after chain extension with cyanuric acid, a chain-extended polyester with a triazine ring as the core is formed, and then end-capped with 3-(2,3-epoxypropoxy)propyltrimethoxysilane to obtain a silane coupling agent-end-capped polyester, and finally peroxyacid oxidation is performed to obtain a modified plasticizer with a large number of epoxy groups. In the process of processing to obtain the composite plastic, the modified plasticizer is embedded in the resin segment to reduce the glass fiber content of the material. The glass transition temperature is increased, thereby increasing its flexibility and fluidity; the large number of benzene ring structures in the modified plasticizer enhance the strength and wear resistance of the plastic, and the silane coupling agent as a capping group further enhances its cross-linking ability with inorganic materials, significantly improving the wear resistance and tensile strength of the composite plastic; further, the large number of epoxy groups in the modified plasticizer absorb the harmful gases released by the resin during the processing of the composite plastic, and at the same time, they polymerize with the free radicals formed by the resin to form a more complex spatial structure of the resin chain segments, thereby significantly improving the strength and tensile strength of the resin.
[0050] 3. In the process of preparing a high-strength wear-resistant composite plastic with a high auxiliary material content, the present invention performs oxidation modification on multilayer graphene, cross-links it with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and further modifies it with a silane coupling agent to obtain a modified filler. The modified graphene is used as the base material of the modified filler. Its excellent specific surface area makes its contact surface with the resin material and the other auxiliary materials wider, and enhances the bonding ability of the other organic materials. At the same time, its excellent physical properties further enhance the strength of the composite plastic. Its rich hierarchical structure also gives it excellent impact resistance, further enhancing the strength of the composite plastic. After oxidation and modification with a silane coupling agent, the compatibility of the multilayer graphene with the organic material is further improved, so that its cross-linking ability with the resin material is further enhanced, and the wear resistance of the composite plastic is further improved. During the processing, a large number of active functional groups of the oxidized graphene react with free radicals generated by the pyrolysis of the resin, so that the adhesion between the modified filler and the resin material is further enhanced, and the strength and wear resistance of the composite plastic are significantly improved. DETAILED DESCRIPTION
[0051] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] This embodiment is used to provide a method for preparing a high-strength wear-resistant composite plastic with a high auxiliary material content, comprising the following steps:
[0054] S1. Preparation of modified plasticizer
[0055] Weigh: 12.0 g 4,4'-stilbene dicarboxylic acid, 6.0 g 1,5-hexadiene-3,4-diol, 75.0 mL dichlorobenzene and 0.6 g 98.0 wt% concentrated sulfuric acid and add them into a reactor. The temperature of the reactor is raised to 150° C. and the reaction is kept warm for 12 hours. After the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid is produced to obtain a modified polyester;
[0056] Weigh: 12.0 g of modified polyester, 12.0 g of cyanuric acid, 50.0 mL of 0.5 wt% sodium hydroxide solution and 45.0 mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 60° C., keep the temperature for 4 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80° C., and distill under reduced pressure until no liquid is produced to obtain a chain-extended polyester;
[0057] Weigh: 24.0 g of chain-extended polyester, 9.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 1.8 g of triethylamine and 120.0 mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 50° C., keep the temperature for 1 hour, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80° C., and distill under reduced pressure until no liquid is produced to obtain a capped polyester;
[0058] Weigh: 27.0g of blocked polyester, 6.0g of formic acid, 6.0g of hydrogen peroxide and 90.0mL of N,N-dimethylformamide, add into a reactor and stir at a stirring rate of 80rpm. The temperature of the reactor is raised to 50°C. After stirring for 30min, the reactor is cooled to room temperature. The reaction liquid is added into a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is extracted to obtain a modified plasticizer.
[0059] S2. Preparation of modified filler
[0060] Weigh: 18.0g of multilayer graphene and 96.0g of 98.0wt% sulfuric acid are added to a reactor at a temperature of 5°C and stirred at a stirring rate of 80rpm. After keeping warm and stirring for 10min, 12.0g of sodium chlorate is added to the reactor. After the reactor temperature is kept at 5°C for 2h, a saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the reactor temperature is raised to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3 times with deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight, to obtain oxidized multilayer graphene;
[0061] Weigh: 18.0 g of graphene oxide, 9.0 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 1.5 g of triethylamine and 75.0 mL of ethanol, add them into a reactor and stir, raise the temperature of the reactor to 50° C., keep warm and stir for 1 hour, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with deionized water 3 times, place the filter cake in a drying oven at 80° C. and vacuum dry until the filter cake has a constant weight, to obtain modified graphene;
[0062] Weigh: 24.0g modified graphene, 9.0g 3-aminopropyltriethoxysilane, 1.8g zinc chloride and 120.0mL N,N-dimethylformamide and add them into the reactor, raise the temperature of the reactor to 50°C, keep the reaction for 30min, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake 3 times with deionized water, place the filter cake in a drying oven at 80°C and vacuum dry it until the filter cake has constant weight to obtain a modified filler.
[0063] S3. Preparation of composite plastics
[0064] Weigh: 45.0 g of polyvinyl fluoride, 16.0 g of modified plasticizer, 12.0 g of modified filler, 3.6 g of diester zinc stabilizer, 3.6 g of butylated hydroxyanisole, 3.6 g of UV-531 and 3.6 g of polyethylene wax, and mix them evenly to obtain a mixture;
[0065] The mixed material is added into a twin-screw extruder, and the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 180°C, 185°C, 185°C, 190°C, 190°C, 200°C, and 200°C, respectively. The main engine speed of the twin-screw extruder is 80 rpm, and the pressure is 100 bar. After melt extrusion, a composite plastic precursor is obtained;
[0066] The plastic precursor is transferred to a box filled with water vapor, treated for 6 hours, cooled and discharged to obtain a composite plastic.
[0067] Example 2
[0068] This embodiment is used to provide a method for preparing a high-strength wear-resistant composite plastic with a high auxiliary material content, comprising the following steps:
[0069] S1. Preparation of modified plasticizer
[0070] Weigh: 12.0 g 4,4'-stilbene dicarboxylic acid, 5.4 g 1,5-hexadiene-3,4-diol, 72.0 mL dichlorobenzene and 0.6 g 98.0 wt% concentrated sulfuric acid and add them into a reactor. The temperature of the reactor is raised to 170°C and the reaction is kept warm for 16 hours. After the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 100°C and distilled under reduced pressure until no liquid is produced to obtain a modified polyester.
[0071] Weigh: 12.0 g of modified polyester, 9.0 g of cyanuric acid, 54.0 mL of 2.0 wt% sodium hydroxide solution and 60.0 mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 80° C., keep the temperature for 6 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100° C., and distill under reduced pressure until no liquid is produced to obtain a chain-extended polyester;
[0072] Weigh: 27.0 g of chain-extended polyester, 12.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 2.1 g of triethylamine and 120.0 mL of N,N-dimethylformamide, add them into a reactor, raise the temperature of the reactor to 60°C, keep the temperature for 2 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain a capped polyester;
[0073] Weigh: 24.0g of blocked polyester, 6.0g of formic acid, 6.0g of hydrogen peroxide and 36.0mL of N,N-dimethylformamide, add into a reactor and stir at a stirring rate of 120rpm. The temperature of the reactor is raised to 60°C. After keeping warm and stirring for 40min, the reactor is cooled to room temperature. The reaction liquid is added into a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is extracted to obtain a modified plasticizer.
[0074] S2. Preparation of modified filler
[0075] Weigh: 18.0g of multilayer graphene and 96.0g of 98.0wt% sulfuric acid are added to a reactor at a temperature of 3°C and stirred at a stirring rate of 120rpm. After keeping warm and stirring for 15min, 12.0g of sodium chlorate is added to the reactor. After the reactor temperature is maintained at 3°C and reacted for 4h, a saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the reactor temperature is raised to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 5 times with deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight, to obtain oxidized multilayer graphene;
[0076] Weigh: 18.0 g of graphene oxide, 7.2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 1.5 g of triethylamine and 75.0 mL of ethanol, add them into a reactor and stir, raise the temperature of the reactor to 60° C., keep warm and stir for 2 h, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with deionized water 5 times, place the filter cake in a drying oven at 80° C. and vacuum dry until the filter cake has a constant weight, to obtain modified graphene;
[0077] Weigh: 24.0g modified graphene, 6.0g 3-aminopropyltriethoxysilane, 1.8g zinc chloride and 120.0mL N,N-dimethylformamide and add them into the reactor, raise the temperature of the reactor to 60°C, keep the reaction for 40min, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake 5 times with deionized water, place the filter cake in a drying oven at 80°C and vacuum dry it until the filter cake has constant weight to obtain a modified filler.
[0078] S3. Preparation of composite plastics
[0079] Weigh: 48.0 g of polyvinyl fluoride, 16.0 g of modified plasticizer, 12.0 g of modified filler, 3.6 g of diester zinc stabilizer, 4.8 g of butylated hydroxyanisole, 4.8 g of UV-531 and 3.6 g of polyethylene wax, and mix them evenly to obtain a mixture;
[0080] The mixed material is added into a twin-screw extruder, and the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 180°C, 185°C, 185°C, 190°C, 190°C, 200°C, and 200°C, respectively. The main engine speed of the twin-screw extruder is 120rpm, and the pressure is 150bar. After melt extrusion, a composite plastic precursor is obtained;
[0081] The plastic precursor is transferred to a box filled with water vapor, treated for 8 hours, cooled and discharged to obtain a composite plastic.
[0082] Example 3
[0083] This embodiment is used to provide a method for preparing a high-strength wear-resistant composite plastic with a high auxiliary material content, comprising the following steps:
[0084] S1. Preparation of modified plasticizer
[0085] Weigh: 10.8 g 4,4'-stilbene dicarboxylic acid, 5.4 g 1,5-hexadiene-3,4-diol, 72.0 mL dichlorobenzene and 0.6 g 98.0 wt% concentrated sulfuric acid and add them into a reactor. The temperature of the reactor is raised to 160°C and the reaction is kept warm for 14 hours. After the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 90°C and distilled under reduced pressure until no liquid is produced to obtain a modified polyester.
[0086] Weigh: 7.2g of modified polyester, 10.8g of cyanuric acid, 45.0mL of 1.0wt% sodium hydroxide solution and 45.0mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 70°C, keep the temperature for 5h, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain a chain-extended polyester;
[0087] Weigh: 27.0 g of chain-extended polyester, 9.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 1.8 g of triethylamine and 120.0 mL of N,N-dimethylformamide and add them into a reactor, raise the temperature of the reactor to 55° C., keep the temperature for 2 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 90° C., and distill under reduced pressure until no liquid is produced to obtain a capped polyester;
[0088] Weigh: 27.0g of blocked polyester, 6.0g of formic acid, 6.0g of hydrogen peroxide and N,N-dimethylformamide, add into a reactor and stir at a stirring rate of 100rpm. The temperature of the reactor is raised to 55°C. After stirring for 35min, the reactor is cooled to room temperature. The reaction liquid is added into a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain a modified plasticizer.
[0089] S2. Preparation of modified filler
[0090] Weigh: 18.0g of multilayer graphene and 90.0g of 98.0wt% sulfuric acid are added to a reactor at a temperature of 0°C and stirred at a stirring rate of 100rpm. After keeping warm and stirring for 12min, 15.0g of sodium chlorate is added to the reactor. After the reactor temperature is kept at 0°C for 3h, a saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the reactor temperature is raised to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 4 times with deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight, to obtain oxidized multilayer graphene;
[0091] Weigh: 18.0 g of graphene oxide, 9.0 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 1.8 g of triethylamine and 75.0 mL of ethanol, add them into a reactor and stir, raise the temperature of the reactor to 55° C., keep warm and stir for 2 h, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with deionized water 4 times, place the filter cake in a drying oven at 80° C. and vacuum dry it until the filter cake has a constant weight, to obtain modified graphene;
[0092] Weigh: 27.0g modified graphene, 9.0g 3-aminopropyltriethoxysilane, 2.4g zinc chloride and 120.0mL N,N-dimethylformamide and add them into the reactor, raise the temperature of the reactor to 55°C, keep the reaction for 35 minutes, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with deionized water 4 times, place the filter cake in a drying oven at 80°C and vacuum dry it until the filter cake has constant weight to obtain a modified filler.
[0093] S3. Preparation of composite plastics
[0094] Weigh: 50.0 g of polyvinyl fluoride, 18.0 g of modified plasticizer, 12.0 g of modified filler, 3.6 g of diester zinc stabilizer, 4.8 g of butylated hydroxyanisole, 3.6 g of UV-531 and 4.8 g of polyethylene wax, and mix them evenly to obtain a mixture;
[0095] The mixed material is added into a twin-screw extruder, and the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 180°C, 185°C, 185°C, 190°C, 190°C, 200°C, and 200°C, respectively. The main engine speed of the twin-screw extruder is 100 rpm, and the pressure is 125 bar. After melt extrusion, a composite plastic precursor is obtained;
[0096] The plastic precursor is transferred to a box filled with water vapor, treated for 7 hours, cooled and discharged to obtain a composite plastic.
[0097] Comparative Example 1
[0098] The difference between this comparative example and Example 3 is that step S1 is eliminated, and in step S3, the composition of the mixture is 50.0 g of polyvinyl fluoride, 6.0 g of modified plasticizer, 4.0 g of modified filler, 1.2 g of diester zinc stabilizer, 1.6 g of butylated hydroxyanisole, 1.2 g of UV-531 and 1.6 g of polyethylene wax.
[0099] Comparative Example 2
[0100] The difference between this comparative example and Example 3 is that step S2 is eliminated, and in step S3, an equal amount of multilayer graphene is used to replace the modified filler.
[0101] Comparative Example 3
[0102] The difference between this comparative example and Example 3 is that the step of preparing the modified filler in step S2 is eliminated, and in step S3, an equal amount of modified graphene is used to replace the modified filler.
[0103] Performance Test:
[0104] The volume wear of the composite plastics prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)";
[0105] The tensile strength of the composite plastics prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber";
[0106] The Izod impact strength of the composite plastics prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 1843-2008 "Determination of Izod impact strength of plastics";
[0107] The vertical burning grades of the composite plastics prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 2408-2021 “Horizontal and vertical methods for determination of burning properties of plastics”;
[0108] The limiting oxygen index of the composite plastics prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 26526-2011 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test";
[0109] With reference to standard GB / T 2917.1-2002 "Determination of hydrogen chloride and any other acidic products released from blends and products based on vinyl chloride homopolymers and copolymers at high temperatures - Congo red method", the release of acidic gases during the preparation of composite plastics in Examples 1-3 and Comparative Examples 1-3 was tested, and the specific data are shown in Table 1.
[0110] Table 1-Performance test data of each sample
[0111]
[0112] Data Analysis:
[0113] Comparing and analyzing the data in Table 1 above, the volume wear loss of the composite plastic prepared by the present invention is 39 mm 3 , tensile strength is 90.5MPa, cantilever beam impact strength is 64.5kJ·m -2 , the vertical combustion grade is V-0, the limiting oxygen index is 45.2%, and the color change time of the Congo red test paper is 852s. All the data are better than those of the comparative example. By comparing the data of Example 3 and Comparative Example 1, it can be found that modifying the auxiliary materials and increasing the content is helpful to improve the performance of the composite plastic;
[0114] By comparing the data of Example 3 with Comparative Examples 2 and 3, it can be found that the modified polyester prepared by the present invention, after chain extension, end-capping and peroxyacid oxidation, the silane coupling agent in the molecular chain segment improves the cross-linking ability of the inorganic material and the plastic, and improves the wear resistance of the composite plastic. The epoxy group generated after the peroxyacid oxidation reacts with the free reaction generated by the cracking of polyvinyl fluoride, while capturing harmful gases, and cross-linking with the polyvinyl fluoride chain segment to enhance the spatial complexity of the polyvinyl fluoride chain segment, so that the tensile strength of the polyvinyl fluoride is significantly enhanced. The triazine group as a chain extender in the interior is carbonized by the acidic substance catalyzed by the decomposition of the flame retardant group in the modified filler at high temperature, further enhancing the flame retardant ability of the composite plastic.
[0115] The modified filler obtained by oxidation, flame retardant cross-linking and silane coupling agent cross-linking of multilayer graphene cooperates with the modified plasticizer to enhance the strength and flame retardant properties of the composite plastic, and finally a wear-resistant, tensile-resistant, flame-retardant and environmentally friendly high-strength composite plastic is prepared.
[0116] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0117] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0118] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-strength wear-resistant composite plastic with a high auxiliary material content, characterized in that: The composition comprises the following components in parts by weight: 40-50 parts of a plastic matrix, 15-20 parts of a modified plasticizer, 10-15 parts of a modified filler, 3-5 parts of a stabilizer, 3-5 parts of an antioxidant, 3-5 parts of an ultraviolet absorber and 3-5 parts of a lubricant; The preparation method of the modified plasticizer comprises the following steps: A1. Add modified polyester, cyanuric acid, 0.5-2.0wt% sodium hydroxide solution and N,N-dimethylformamide into a reactor, raise the temperature of the reactor to 60-80°C, keep the temperature for 4-6h, and post-treat to obtain chain-extended polyester; A2, adding chain-extended polyester, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 50-60° C., keeping the temperature for reaction for 1-2 hours, and post-treating to obtain a capped polyester; A3. Add the end-capped polyester, formic acid, hydrogen peroxide and N,N-dimethylformamide into a reaction kettle and stir. The temperature of the reaction kettle is raised to 50-60°C. After stirring for 30-40 minutes, post-treatment is performed to obtain a modified plasticizer.
2. A high-strength wear-resistant composite plastic with high auxiliary material content according to claim 1, characterized in that: In step A1, the amount ratio of the modified polyester, cyanuric acid, 0.5-2.0wt% sodium hydroxide solution and N,N-dimethylformamide is 2-4g:2-4g:15-20mL:15-20mL; in step A2, the amount ratio of the chain-extended polyester, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide is 8-10g:2-4g:0.5-0.8g:40-60mL; in step A3, the stirring rate is 80-120rpm, and the amount ratio of the end-capped polyester, formic acid, hydrogen peroxide and N,N-dimethylformamide is 8-10g:1-2g:1-2g:30-40mL.
3. The high-strength wear-resistant composite plastic with high auxiliary material content according to claim 1, characterized in that: In step A1, the preparation method of the modified polyester is: 4,4'-stilbene dicarboxylic acid, 1,5-hexadiene-3,4-diol, dichlorobenzene and 98.0wt% concentrated sulfuric acid are added to a reactor, the temperature of the reactor is increased to 150-170°C, the reaction is kept warm for 12-16h, and the modified polyester is obtained by post-treatment.
4. A high-strength wear-resistant composite plastic with high auxiliary material content according to claim 3, characterized in that: The dosage ratio of the 4,4'-stilbene dicarboxylic acid, 1,5-hexadiene-3,4-diol, dichlorobenzene and 98.0wt% concentrated sulfuric acid is 2-4g:1-2g:20-30mL:0.1-0.2g. The post-treatment comprises: after the reaction kettle is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100°C, and the modified polyester is obtained by distillation under reduced pressure until no liquid is produced.
5. The high-strength wear-resistant composite plastic with high auxiliary material content according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: B1. Add graphene oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, triethylamine and ethanol into a reactor and stir. Raise the temperature of the reactor to 50-60° C., keep warm and stir for 1-2 hours, and perform post-treatment to obtain modified graphene. B2. Add modified graphene, 3-aminopropyltriethoxysilane, zinc chloride and N,N-dimethylformamide into a reactor, increase the temperature of the reactor to 50-60° C., keep the temperature for 30-40 minutes, and perform post-treatment to obtain a modified filler.
6. A high-strength wear-resistant composite plastic with high auxiliary material content according to claim 5, characterized in that: In step B1, the stirring rate is 80-120rpm, and the amount ratio of the graphene oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, triethylamine and ethanol is 5-8g:2-3g:0.5-0.6g:25-35mL; in step B2, the amount ratio of modified graphene, 3-aminopropyltriethoxysilane, zinc chloride and N,N-dimethylformamide is 8-10g:2-4g:0.5-0.8g:40-50mL.
7. A high-strength wear-resistant composite plastic with high auxiliary material content according to claim 6, characterized in that: The preparation method of the graphene oxide is as follows: multilayer graphene and 98.0wt% sulfuric acid are added to a reactor at a temperature of 0-5°C and stirred, and after heat preservation and stirring for 10-15 minutes, sodium chlorate is added to the reactor, and the temperature of the reactor is kept at 0-5°C for reaction for 2-4 hours, and a saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7, and post-processing is performed to obtain the multilayer graphene oxide.
8. The high-strength wear-resistant composite plastic with high auxiliary material content according to claim 7, characterized in that: The multilayer graphene, 98.0wt% sulfuric acid and sodium chlorate are used in a ratio of 5-8g:30-40g:3-5g, and the stirring rate is 80-120rpm. The post-treatment includes: after the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed with deionized water for 3-5 times, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight, to obtain oxidized multilayer graphene.
9. The method for preparing a high-strength wear-resistant composite plastic with high auxiliary material content according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Evenly mixing a plastic matrix, a modified plasticizer, a modified filler, a stabilizer, an antioxidant, an ultraviolet absorber and a lubricant to obtain a mixture; S2, adding the mixed material to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 180°C, 185, 185°C, 190°C, 190°C, 200°C, 200°C, the main engine speed of the twin-screw extruder is 80-120rpm, the pressure is 100-150bar, and a composite plastic precursor is obtained after melt extrusion; S3. Transfer the plastic precursor to a box filled with water vapor, treat it for 6-8 hours, cool it down and discharge it to obtain a composite plastic.
Citation Information
Patent Citations
Novel rubber and thermoplastic multi-component systems rubber and thermoplastic composite moulded pieces made therefrom method for production and use thereof
CN101374890A
High-strength wear-resistant polypropylene composite material and preparation method thereof
CN112679844A
Degradable wear-resistant plastic woven bag and preparation method thereof
CN116536822A
Fireproof powder coating with antistatic effect and preparation method thereof
CN118185433A
Cited By
Preparation method of nano reinforced and toughened ultraviolet-resistant plastic material
CN119592034A
Flame-retardant aging-resistant cable for solar power generation and preparation method thereof
CN120137409A
